OPTIMIZING TRIAGE PROTOCOLS IN EMERGENCY NURSING: A CRITICAL ANALYSIS FOR IMPROVED PATIENT OUTCOMES. - Ali Mohammed Abdullah, Mohammed Ahmad Alasseri, Saleh Mohmmed Ali Alyami, Raid Mohammad abdullahalajam, Tareq Husain Alqanas, Mahdi Mohammed Ali A, Hussain Ali QohsanAlyami (Chelonian Research Foundation, 2023)
This article comprehensively assesses triage Protocols in critical care to progress the understanding of results. The objective is to make strides in the triage handle through a combination of writing audits, handling audits, result examination, and handling proposals. Combining evidence-based hone with progressed techniques, this study offers a perspective on quickly expanding crisis care's viability and effectiveness. A comprehensive writing survey analyzes accessible Protocols to decide their qualities, shortcomings, and effect on persistent well-being. The strategies employ a blended and comprehensive approach to information collection, test choice, and examination to assess current strengths and propose ways to make strides. Inquire about comes about are displayed through quantitative and subjective information examination upgraded with graphical representation. The study translates these ideas based on existing writing and considers suggestions for honed, approached, and future research.